PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN LIVEWORKSHEET - Febrianti, Dian Wahyu; Fauziah, An Nuril Maulida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement of students’ problem-solving skills through the implementation of the Problem Based Learning (PBL) model assisted by LiveWorksheet on the digestive system topic. This research employed a quantitative approach with a pre-experimental design using a one group pretest-posttest design. The subjects of this study were 25 students of class VIII D at Junior High School 1 Paciran in the 2025/2026 academic year. The research instrument consisted of essay tests based on Polya’s problem-solving indicators, namely understanding the problem, devising a plan, carrying out the plan, and looking back. Data analysis was conducted using the N-gain test and and paired statistical tes to determine the improvement in students’ problem-solving skills. The results showed that students’ problem-solving skills improved after the implementation of the learning model. A total of 56% of students were categorized as high, while 44% were in the medium category. Furthermore, the N-gain results for each indicator showed improvement with medium to high categories, namely understanding the problem (0.63), devising a plan (0.60), carrying out the plan (0.71), and looking back (0.73). Therefore, it can be concluded that the implementation of the PBL model assisted by LiveWorksheet is effective in improving students’ problem-solving skills.